1993
DOI: 10.1177/0022427893030003002
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Recidivism of Florida's Community Control and Prison: A Five-Year Survival Analysis

Abstract: Florida's Community Control Program is the nation's largest intermediate sanction (home confinement) program for felons. The question addressed in this research is the effectiveness of this sanction compared to imprisonment, as measured by recidivism. The rearrest, reconviction, imprisonment, and recidivism survival of the first cohort of convicted felons sentenced to Community Control were tracked for nearly five years and compared to the recidivism of a partially matched group of convicted felons released fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 13 publications
1
20
0
1
Order By: Relevance
“…For example, Muiluvuori (2001) found in a study conducted in Finland that 60.5% among those sentenced to community service re-offended during the follow-up period of 5 years, compared to 66.7% among those who served a custodial sentence. Though not significant, this difference is in line with findings from the Netherlands (Spaans 1998), Australia (Roeger 1994), and the United States (Smith and Akers 1993). Some authors also concluded that community service is particularly suitable for offenders without previous prison experience (Muiluvuori 2001).…”
supporting
confidence: 79%
“…For example, Muiluvuori (2001) found in a study conducted in Finland that 60.5% among those sentenced to community service re-offended during the follow-up period of 5 years, compared to 66.7% among those who served a custodial sentence. Though not significant, this difference is in line with findings from the Netherlands (Spaans 1998), Australia (Roeger 1994), and the United States (Smith and Akers 1993). Some authors also concluded that community service is particularly suitable for offenders without previous prison experience (Muiluvuori 2001).…”
supporting
confidence: 79%
“…We next explain the details of the specific mechanics of how a precision matching dataset of prison and Community Control cases was created from the 144,416 cases on a step-by-step basis. The reason for a detailed explanation is because most prior studies examining the effect of imprisonment on recidivism using this methodology fail to explain the technicalities associated conducting precision matching (Kraus 1974(Kraus , 1978(Kraus , 1981Muiluvuori 2001;Savoainen 1968;Smith and Akers 1993; for an exception, see Petersilia et al 1986). 8 This is problematic since readers may not be able to assess the accuracy of the precision matching process and to assist those who seek to replicate or improve upon previously used methods.…”
Section: Precision Matchingmentioning
confidence: 99%
“…Fourth, the datasets were merged with SAS using the matched variable as the identifier and a variable was created indicating if each record was in both the prison and Community Control files, only in the prison file, or only in the Community Control file. Fifth, only cases 8 An example of the lack of information relating to the precision matching process is the study of the effectiveness of Florida's Community Control program versus prison in terms of recidivism conducted by Smith and Akers (1993). Their Table 1 (p.276) displays differences in summary statistics across the two punishment groups with sample sizes of 228 in the Community Control group and 266 in the prison group.…”
Section: Precision Matchingmentioning
confidence: 99%
“…2 Criminologists and sociologists from various traditions have argued that integration into one's community and a complex network of social ties decreases the likelihood of deviant behavior (for example, anomie theory, Merton, 1938;social control theory, Hirschi, 1969;strain theory, Agnew, 1985). Following in the same vein, Smith and Akers (1993) compared recidivism rates of incarcerated male offenders with their counterparts on CC. They concluded that neither model of punishment works to reduce recidivism.…”
Section: Recommendationsmentioning
confidence: 99%